Decoding Data - A. Qureshi, M.; Atif, Amara; Yang, Yang; Jha, Meena; MWAGWABI, FLORENCE; Papini, Marcella (UTS ePRESS, 2026)
In an era where data-driven decision-making is paramount, “Decoding Data: A Complete Guide to Business Intelligence” serves as an essential Open Educational Resource (OER) tailored for both students and professionals seeking to develop a deep understanding of Business Intelligence (BI) strategies. This resource aims to empower learners with the knowledge and skills necessary to harness the full potential of BI in the modern business landscape. This comprehensive resource covers a wide spectrum of BI topics, including data to knowledge continuum, systems for decision support, the architecture of BI, business analytics, reporting, and emerging technologies. An innovative pedagogical approach combines theoretical concepts with practical skills for effective data utilisation by creating reports, visualisations, and dashboards, offering readers a holistic understanding of BI concepts. With hands-on exercises and real-world case studies, “Decoding Data: A Complete Guide to Business Intelligence” goes beyond traditional learning methods, providing interactive tools that engage and challenge the reader. The content is organised as a roadmap, guiding readers through the complexities of BI implementation, starting from foundational concepts and progressing seamlessly toward advanced data analytics. This journey equips users with theoretical groundwork and practical skills directly applicable across diverse business scenarios. The book’s focus on key concepts and theories ensures users a sophisticated comprehension of BI, enhancing their analytical skills and decision-making capabilities. More than a textbook, “Decoding Data: A Complete Guide to Business Intelligence” is a pathway to enhancing analytical skills, refining decision-making abilities, and cultivating a profound appreciation for BI’s pivotal role in driving organisational success. This resource promises not just knowledge acquisition but tangible skills development. Embark on a transformative journey with “Decoding Data: A Complete Guide to Business Intelligence”, where theory meets practice, and education evolves into actionable insights.